Asymmetric return response to expected risk: policy implications. Issue 3 (8th July 2019) - Dicle, Mehmet F.; Reed, Kendra
Abstract : Purpose: As investors' fear has an impact on their risk-return tradeoff, this fear leaves markets susceptible to sudden and large fluctuations. The purpose of this study is to suggest regulators to amend their precautionary methods to recognize the difference in investor behavior for high-risk periods versus low-risk periods. Design/methodology/approach: The authors empirically show the difference in investor response to changes in expected risk as a function of level of risk. They then show different return patterns for high-risk and low-risk days. Their approach is implemented to evaluate whether investors' reaction is the same to changes in risk during high-risk versus low-risk periods. Findings: The results indicate that the negative return response to incremental increases in risk is significantly higher for periods of high versus low expected risk, with high defined as risk levels above long-run normal. Research limitations/implications: Investors' increased response to changes in risk exposes financial markets to higher likelihood of sudden and larger fluctuations during high-risk periods. Regulator-imposed circuit breakers are designed to protect markets against such market crashes. However, circuit breakers are not designed to account for investor behavior changes. The results show that circuit breakers should be different for high- versus low-risk periods. Practical implications: A circuit breaker that is designed to protect investors against large drops should be amended to have a lower threshold during high-risk periods. Originality/value: The contribution is, to the authors' knowledge, the first research effort to evaluate the effects of differences in investor behavior on investor reactions and regulator imposed fail-safes. During the times of extreme market risk, the proposed changes may enable circuit breakers function their intended purposes.